Evaluation of Knowledge Regarding to Oral Manifestation of AIDS among General Dentists in Kermanshah, 2014 - neda Omidpanah; najmeh salehifar (Fasa University of Medical Sciences, 2015)
Background & Objective: Oral lesions are the primary manifestations of HIV infections. The aim of this study is to evaluate the knowledge towards oral manifestations of AIDS among general dentists.   Materials & Methods: This cross-sectional study has been conducted by a self-administrated questionnaire on general dentists in Kermanshah city, 2014. The questionnaire contained demographic information and the part assessing knowledge. The correct answers in percent was considered as the knowledge level, that was classified by poor, intermediate, good, and excellent levels. The questionnaire reliability was confirmed by Cronbach alpha=0.79. Data were analyzed by SPSS 17 by using ANOVA, tukey and t-test (P< 0.05).   Results: A total of 120 general dentists including 76 males (63.3%) and 44 females (36.7%) with mean age of 36.4±9.3 years completed the questionnaires. Of the dentists, 1.7% presented excellent, 23.3% good, 48.3% intermediate, and 26.7% poor level regarding to total knowledge about AIDS/HIV. With respect to AIDS-related oral lesions, only 7.5% had excellent and 9.2% displayed good knowledge. Among dentists, intermediate and poor levels were observed in 35% and 48.3%, respectively. The dentists' knowledge of AIDS-related oral manifestations revealed no significant relationship to age, gender, work experience, or attendance in educational workshops (P>0.05).   Conclusion: The dentists' knowledge about oral lesions of AIDS was not in an acceptable level, suggesting improvement of their awareness about AIDS/HIV and its oral lesions.